Modeling and Optimization of Electric Discharge Machining Process Parameters in machining of Al 6061/SiCp Metal Matrix Composite. (2021) - Srivastava, Anjani; Yadav, Sunil Kumar; Singh, D.K.
Abstract: The present work deals with EDM machining of Aluminium metal matrix composite (MMC) Al 6061 reinforced with 8% wt SiC particle which was fabricated in house by stir casting process. Fabricated MMC was machined by ZNC Electric Discharge Machining (EDM). Response surface methodology (RSM) was used for mathematical modelling and optimization of process parameters such as peak current, pulse on time and duty cycle. Box-Behnken Design (BBD) approach was used to create experimental design. Mathematical model was developed between selected input process parameters and responses such as Material Removal Rate (MRR), Electrode Wear Rate (EWR) and Surface Roughness (SR). Analysis of variance (ANOVA) was carried out to find significance of process parameters. The theory of desirability was used for choosing the optimal combination of process parameter.